Da escrita da vida como construção ficcional : perspectivas de leitura de Florbela Espanca, de Agustina Bessa-Luís - Furlan, Vivian Leme (Universidade Federal de São Carlos, 2016)
Published in 1979, the work Florbela Espanca: vida e obra, by Agustina Bessa-Luís, shows itself as a complex characterization text to fitness in a unique literary genre, due to compose, in a first aspect, a narration of life. However, it is clear that it is not just from a pure character and simply biographical, suggesting a fluid possibility between referentiality and fictional categories. For this, the presented concerns revolve around the question how Agustina’s work feed in a hybrid communion of different textual categories. Our interests are, also, observe how this kind of genre complexity is an occurrence in author conception, mainly in the Portuguese scene after the Revolução dos Cravos placing it thus in line with female authors, allowing a contemporary work analysis, in addition to their compliance with certain neobarroco procedures that approaches the textual structure to a kaleidoscope image and its effects in the whole composition.
Keywords: Biografismo; Escrita de autoria feminina; Agustina Bessa-Luís; Biographism; Female authors writing; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURAS ESTRANGEIRAS MODERNAS; LINGUISTICA, LETRAS E ARTES